2005
DOI: 10.1093/nar/gni053
|View full text |Cite
|
Sign up to set email alerts
|

Correcting errors in synthetic DNA through consensus shuffling

Abstract: Although efficient methods exist to assemble synthetic oligonucleotides into genes and genomes, these suffer from the presence of 1–3 random errors/kb of DNA. Here, we introduce a new method termed consensus shuffling and demonstrate its use to significantly reduce random errors in synthetic DNA. In this method, errors are revealed as mismatches by re-hybridization of the population. The DNA is fragmented, and mismatched fragments are removed upon binding to an immobilized mismatch binding protein (MutS). PCR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
62
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(63 citation statements)
references
References 30 publications
1
62
0
Order By: Relevance
“…Antibiotic-resistance genes or synthetic DNA (or cDNA) molecules fused to antibiotic-resistance genes were selected for viability to reduce errors in synthetic genes from the surviving clones. [3,4,[13][14][15][16] We examined the source of gene synthesis errors from previously reported data, [5,7,9,[17][18][19] and confirmed that nucleotide deletions and insertions are major culprits. On average, deletion and addition account for more than 70 % of errors in most of the reported gene syntheses ( Figure S1 in the Supporting Information).…”
Section: Introductionmentioning
confidence: 53%
“…Antibiotic-resistance genes or synthetic DNA (or cDNA) molecules fused to antibiotic-resistance genes were selected for viability to reduce errors in synthetic genes from the surviving clones. [3,4,[13][14][15][16] We examined the source of gene synthesis errors from previously reported data, [5,7,9,[17][18][19] and confirmed that nucleotide deletions and insertions are major culprits. On average, deletion and addition account for more than 70 % of errors in most of the reported gene syntheses ( Figure S1 in the Supporting Information).…”
Section: Introductionmentioning
confidence: 53%
“…One such group of methods relies on the sequence mismatch recognition capabilities of the MutS protein to specifically bind to sequence mismatches in synthetic DNA duplexes. Selective binding of MutS to error-containing DNA can be used to sieve error-free sequences from those that contain errors (Carr et al 2004;Binkowski et al 2005;Wan et al 2014). These methods usually immobilize MutS to a solid matrix material and then purify column-bound (error-containing) DNA sequences from unbound material (error-reduced).…”
Section: Error Correction and Sequence Validationmentioning
confidence: 99%
“…The mismatch cleaving proteins (2) cleave mismatch regions within incorrect DNA complexes. The cleaved complexes can be built into an error-free complex by a polymerase chain assembly (Binkowski et al, 2005) of removed by size selection or exonuclease degradation (Bang, Church, 2008). A combination of mismatch-specific endonucleases such as single-strand-specific nucleases S1 and P1, mung bean nuclease and CEL I nuclease (Desai, Vepatu, 2003), mismatch repair endonuclease MutH (Smith, Modrich, 1997), and resolvases, such as T7 endonuclease I, E. coli endonuclease V and T4 endonuclease VII (Ma et al, 2012a) can be used for error removal from synthetic genes.…”
Section: Correction Of Errors From Synthetic Genesmentioning
confidence: 99%